The Fiscal deficit in Ecuador and its repercussion on health service expenditure. Period 2015-2018 (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
This study addresses and analyzes the impact of the fiscal deficit with respect to spending on services and expenditures considered as health investment in Ecuador during the period 2015–2018, based on the budgetary evolution assigned to said sector, taking into account the two last presidential administration periods in the country and their changes in fiscal policies. The basis of the study is the compilation of documentary, statistical and qualitative information. The methodologies used are exploratory and descriptive, due to their scientific relevance and applicability in this work. As a main result, it is determined that the State, has not yet managed to fully guarantee the right to health, faithfully complying with the parameters of gratuitousness and universality, despite the deployment of great efforts and elaboration of macro social plans, shows that if significant development progress has been made in health, however, this has not been done in a sustainable way; This is where the fiscal deficit tends to increase the size of the fiscal gap. Faced with this situation, the State requires the reform of an Economic Program in a holistic context, which, within the framework of a dollarized economy, seeks to achieve a fiscal balance to maintain a coherent, harmonious economic system that translates into health as a sustainability axis to achieve faithful compliance with the parameters of the state that guarantees constitutional rights in force since 2008, free and universal.
Keywords: deficit; fiscal; impact; investment; spending; health; Ecuador